Determination of fuzzy logic membership functions using genetic algorithms - Arslan, A; Kaya, M (Elsevier Science Bv, 2001)
Genetic algorithm (GA) is an adaptive search technique based on natural selection and genetic rules. GA takes place in various scientific applications and it can be also used to determine the membership functions in a fuzzy system. The aim of the study is to adjust the shape of membership functions and a novice aspect of the study is to determine the kind of membership functions. Proposed method has been implemented using a developed GA program for a single input and output fuzzy system. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: genetic algorithms; membership functions; optimization